Les guichets du Louvre Based on a Story by Roger Boussinot - Mitrani, Michel; Tournier, Jean; Rist, Christian; Pascal, Christine; Garcin, Henri (KVP, 2007)
In Paris, in 1942, on a Thursday, the Parisian police herded together some 13,000 Jews for deportation to German territory. In this story, Paul (Christian Rist) is a teenager who tries to prevent this from happening. At first he attempts to save two elderly Jews, but they are resigned to their fate and comply with the order to assemble. For a short while, he is able to keep Jeanne (Christine Pascal) from joining them, but, after a long and strenuous day, she finally escapes from him he is too tired to chase after her. [Clarke Fountain, All Movie Guide]